Designing a Training Program for Faculty Members at Al-Isra University Based on the Standards of Quality Assurance - Tannous, Intesar (Dirasat: Educational Sciences, 2021)
This study aims to present a proposal for a training program based on the needs of Al Isra university faculty members in the light of the standards of quality assurance. To achieve the aim of the study, the researcher prepared a questionnaire consisting of (54) items, each of which represents a training need in the following areas: planning and teaching, measurement and evaluation, scientific research, community service, and leadership and academic management. It was applied to a sample of (119) faculty members in all scientific and humanitarian faculties at Al-Isra University. The researcher used a descriptive, analytical method to answer the research questions. The findings revealed a high need in all of the domains of the study. Moreover, the results of statistical analysis showed that there are statistically significant differences in the training needs attributed to the variable of academic rank. The Center for the Development of Academic Staff Performance and the Office of Quality Assurance at the University of Isra should design courses and professional development programs for faculty members and work to develop their performance.